Profil Kemampuan Manajemen Waktu Peserta Didik Pada Kelas IX di SMPN 13 Kota Padang - Zakiyah, Mutia; Chandra, Yasrial; Dwi Putri, Besti Nora (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This study aims to describe the Time Management Ability Profile of Students in Grade IX at SMPN 13 Padang City. This study is a quantitative descriptive research that aims to describe how the time management of students at SMP Negeri 13 Padang is described. The research population is all students in grade IX of SMP Negeri 13 Padang which totals 293 students. The research sample was determined using a purposive sampling technique of 58 students. The data collection tool was used a questionnaire, and it was processed using a percentage technique. The results of the study can be described as follows: 1) The profile of students' time management skills is seen from the aspect of setting goals to be in the good category 2) The profile of students' time management skills is seen from the aspect of Setting Priorities to be in the good and fairly good category which is balanced 3) The profile of students' time management skills is seen from the aspect of being firm towards the very good category. 4) The profile of students' time management skills in the aspect of avoiding delays against the good category. The time management of students in studying at SMP Negeri 13 Padang has not reached the maximum level because there is still a very good category level.